7 tenets of Taxi Terry : how every employee can create and deliver the ultimate customer experience - McKain, Scott (McGraw Hill-Ascent Audio, 2014)
Defeat your company's greatest enemy: employee disengagement 7 Tenets of Taxi Terry outlines seven essential keys to engagement that any one at any job can use to excel. McKain threads them all together with the story of Taxi Terry, a cab driver in Jacksonville, FL, who gave him the best customer service experience of his life. Scott empowers you to make a tangible difference in your own life and the lives of your customers and contribute to overall health of the organization. Scott McKain has been recognized by Social Media Marketing Magazine as one of the 50 most influential marketing authors on Twitter. A popular keynote speaker on creating more compelling customer connections, McKain is a member of the Professional Speakers Hall of Fame.